Analysis of The Relationship Between Pay Level Satisfaction and Individual Work Performance With Person–Environment Fits (Person–Job Fit, Person–Organisation Fit, and Person–Group Fit) as Moderating Variables - Hardiyanto, Dedy; Hendarsjah, Hidajat (The Asian Journal of Technology Management (AJTM), 2021)
In this study, we examined the effect of pay level satisfaction on individual work performance moderated by person–environment fits, namely person–job fit, person–organisation fit, and person–group fit. This study used a survey questionnaire of 297 conductors of PT Kereta Api Indonesia Persero. The study results show that pay level satisfaction has a positive and significant association with individual work performance. In contrast, person–environment fit does not affect individual work performance, as the unsupported analysis results evidence. This article concludes with directions for future research on the relationships among pay level satisfaction, person–environment fit, and individual work performance and their various implications for management practice.